(untitled) (Diversification: Journal of Economics and Management Studies, 2024)
This study aims to determine the effect of discipline and work motivation on employee performance with job satisfaction as an intervening variable in PT. PGAS Solution Area Riau. This research was carried out with a quantitative approach with data collection methods through surveys and distributing questionnaires, with a sample of 60 respondents using the random sampling method, namely the population has the same opportunity to be selected as a sample. The analysis method used is Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS). For hypothesis testing, Path Coeficient is used, which is a test carried out to see direct influences, and Indirect Effect is a test that aims to see indirect influences. The results of data analysis show that there is a positive and significant influence between work disciplines on job satisfaction. There is a positive and significant influence between work motivation and job satisfaction. There is a positive and significant influence between work discipline on employee performance. There is a negative and insignificant influence between work motivation and performance at PT. PGAS Solution Area Riau